Correlation of Cyber Law with Civil Law: Theoretical and Practical Studies - Abdurrahman, U. (International Journal of Sustainability in Research, 2024)
This research aims to examine the correlation and relationship between Cyberlaw and Civil Law with a theoretical and practical approach. This research uses qualitative methods, which specifically examine normative juridical matters regarding Cyber Law and examine its technical aspects. With in-depth study, shows that Cyber Law and Civil Law have a very close relationship, both individuals and institutions, which includes aspects of security and protection of personal identity, proof and accountability in the eyes of the law, and concludes that electronic documents and their technical use have not been regulated, so it is necessary strengthening and improving the law, so that there is no legal vacuum or uncertainty.